#Frailty: A snapshot Twitter report on frailty knowledge translation. (7th May 2018) - Jha, Sunita R; McDonagh, Julee; Prichard, Ros; Newton, Phillip J; Hickman, Louise D; Fung, Erik; Macdonald, Peter S; Ferguson, Caleb
Abstract : Objectives: The objectives of this short report are to: (i) explore #Frailty Twitter activity over a six‐month period; and (ii) provide a snapshot Twitter content analysis of #Frailty usage. Methods: A mixed‐method study was conducted to explore Twitter data related to frailty. The primary search term was #Frailty. Objective 1: data were collected using Symplur analytics, including variables for total number of tweets, unique tweeters (users) and total number of impressions. Objective 2: a retrospectively conducted snapshot content analysis of 1500 #Frailty tweets was performed using TweetReach ™ . Results: Over a six‐month period (1 January 2017–31 June 2017), there was a total of 6545 #Frailty tweets, generating 14.8 million impressions across 3986 participants. Of the 1500 tweets (814 retweets; 202 replies; 484 original tweets), 56% were relevant to clinical frailty. The main contributors ('who') were as follows: the public (29%), researchers (25%), doctors (21%), organisations (18%) and other allied health professionals (7%). Tweet main message intention ('what') was public health/advocacy (41%), social communication (28%), research‐based evidence/professional education (24%), professional opinion/case studies (15%) and general news/events (7%). Conclusions: Twitter is increasingly being used to communicate about frailty. It is important that thought leaders contribute to the conversation. There is potential to leverage Twitter to promote and disseminate frailty‐related knowledge and research.